Cardiac surgeryThe use of negative pressure wound therapy in the treatment of wound infections – a single-center 12-month experience - Kępa, Krzysztof; Krzych, Łukasz; Wacławczyk, Tomasz; Krejca, Michał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background : The prevalence of surgical site infections (SSI) in cardiac surgery is about 0.5-10%, according to different sources, and leads to a prolonged hospital stay and higher mortality. The aim of the study was to describe the clinical outcomes of our 12-month experience using negative pressure wound therapy (NPWT). Material and methods: We performed a retrospective analysis of 32 patients undergoing NPWT between October 1, 2011 and September 30, 2012 (i.e. 2.7% of all patients who underwent surgical treatment in this period). Patient characteristics, risk factors, and procedure-related variables were analyzed and compared in two groups: group 1 included patients with infection of skin and subcutaneous tissue (1.2%), while group 2 consisted of patients with mediastinitis (1.6%). Results : Mediastinitis was three times more frequent among women (p = 0.09) and diabetics (p = 0.08), and four times more frequent in patients with chronic obstructive pulmonary disease (p = 0.2). The most frequently performed procedure was coronary artery bypass grafting (87.5%). Methicillin-resistant Staphylococcus epidermidis (26.2%) and Pseudomonas aeruginosa (21%) were the pathogens that were most frequently isolated from the infected wounds. The mean time of hospitalization was 64 ±35 days, which was similar in the two studied groups. In-hospital mortality in the mediastinitis group was 16.7%; no deaths were related to the use of NPWT therapy. Results: Our findings indicate that NPWT is a viable option for SSI treatment. Moreover, the use of NPWT may lower patient mortality, as well as reduce the length and costs of hospitalization. In order to achieve this, however, it is necessary to diagnose the infection early and to implement adequate treatment.